2023
DOI: 10.3389/fbioe.2023.1162684
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive ex vivo and in vivo preclinical evaluation of novel chemo enzymatic decellularized peripheral nerve allografts

Abstract: As a reliable alternative to autografts, decellularized peripheral nerve allografts (DPNAs) should mimic the complex microstructure of native nerves and be immunogenically compatible. Nevertheless, there is a current lack of decellularization methods able to remove peripheral nerve cells without significantly altering the nerve extracellular matrix (ECM). The aims of this study are firstly to characterize ex vivo, in a histological, biochemical, biomechanical and ultrastructural way, three novel chemical-enzym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 77 publications
0
3
0
1
Order By: Relevance
“…Thus, it was possible to evaluate their ability to withstand stretch deriving from the formation of external fibrotic tissue, and if they are easy-to manipulate for clinicians [15,57]. Previous studies [37,58,59] have indicated that the Young's modulus of rat sciatic nerves varies between 10.19 and 18.66 MPa, which coincides with the Young's modulus values of FF scaffolds. The PLA and PCL scaffolds showed significant stiffness, which could potentially affect the nerve tissue structure and neuronal networks; however, this it could be addressed by blending these polymers with softer biomaterials to achieve more suitable viscoelastic properties [60].…”
Section: Discussionmentioning
confidence: 67%
“…Thus, it was possible to evaluate their ability to withstand stretch deriving from the formation of external fibrotic tissue, and if they are easy-to manipulate for clinicians [15,57]. Previous studies [37,58,59] have indicated that the Young's modulus of rat sciatic nerves varies between 10.19 and 18.66 MPa, which coincides with the Young's modulus values of FF scaffolds. The PLA and PCL scaffolds showed significant stiffness, which could potentially affect the nerve tissue structure and neuronal networks; however, this it could be addressed by blending these polymers with softer biomaterials to achieve more suitable viscoelastic properties [60].…”
Section: Discussionmentioning
confidence: 67%
“…Studies involve assessing the regenerative potential of various decellularization protocols on animal models to understand their effectiveness in nerve regeneration. This research is crucial for advancing the treatment of severe nerve injuries where traditional methods may not be sufficient ( Garcia-Garcia et al, 2023 ). Decellularized nerve grafts should provide a suitable substrate for nerve regeneration in which the conservation of ECM components plays a crucial role for peripheral nerve regeneration and axonal guidance ( Hsu et al, 2023 ; Mahdian et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although dECM derived from tissues have biochemical and physical factors that support the growth of cells and tissues [ 32 ], the consistent provision of quality donor tissue constitutes a prominent constraint. Recognized challenges linked to tissue-derived dECM comprise pathogen transmission, uncontrolled degradation, and high manufacturing costs [ [33] , [34] , [35] ]. Nevertheless, the cell-based dECM with more advantages can be used to engineer scaffolds with different three-dimensional shapes and structures and other additional features to produce biomimetic tissue structures, and can be customized by selecting specific cells from a particular tissue or individual to overcome the limitations of homo- or xenotransplantation.…”
Section: Discussionmentioning
confidence: 99%